LOCAL POLITICAL DYNAMICS IN THE GENERAL ELECTION DIRECTLY CONDUCTED TO VOTE FOR DISTRICT HEADS (PILKADA) IN BADUNG REGENCY IN 2005 - Wisnumurti, A.A. Gede Oka (E-Journal of Cultural Studies; Vol 17 No 1 (2024): Volume 17 Number 1 February 2024, 2024)
The general election directly conducted to vote for the regent and vice regent ( Pemilihan Kepala Daerah , abbreviated to Pilkada ) by the people in Badung Regency in 2005 was the first one. The people’s direct involvement in the local political life moved highly dynamically. The struggle for power by various strengths affected various dimensions of the people’s lives; therefore, it is interesting to investigate the local political dynamics in the Pilkada directly conducted in Badung Regency in 2005 in the perspective of cultural studies. There are three problems formulated in this study. They are (1) what was the dynamics of the Pilkada directly conducted in Badung Regency in 2005 like?; (2) how the relation of strengths affected the local political dynamics in the Pilkada directly conducted in Badung Regency in 2005?; (3) what were the implications and meanings of the local political dynamics of the Pilkada directly conducted in Badung Regency in 2005? The results of the study show that fluctuative changes took place continuously with regard to the form and functions of societal structure. Culturally, the people’s ideology changed from being mono centric into being multi centric. The relation of strengths became segmented into three main strengths forming a new formation of strength referred to as trisula.   This led to an institutional configuration, differentiation of power and locality sedimentation, and provided meanings to competition and tolerance, emancipatory, political comodification, adaptive leadership and local democratic cultural strengthening. Keywords : dynamics, local politics, and direct pilkada in Badung Regency